Tugas Mandiri Siswa sebagai Implementasi Pembelajaran Kurikulum 2013 untuk Peningkatan Kualitas Mengajar Guru - Muhamad Noor Wijayanto; Sri Utaminingsih; Much Arsyad Fardani (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The background of this research is that students have difficulty understanding subjects, the process is not as expected, students pay less attention to teacher explanations while studying at school, and students do not complete teacher assignments. The aim of the study was to analyze the form of independent assignments for elementary school students at SD N 2 Rendeng Kudus in terms of the concept of learning theory. The method used is descriptive qualitative. The results showed that structured assignments were used by the teacher as a student s independent task with the concept of behavioristic learning theory in learning at SD N 2 Rendeng because the teacher used teacher centered learning. With these results it is expected that teachers can improve the quality of teaching in the use of media and learning models in accordance with the 2013 curriculum.